Pengaruh Waktu Istirahat Berbeda Sebelum Proses Pemotongan Terhadap Respon Suhu Permukaan Tubuh Sapi Brahman Cross - M. Adhyatma; Gayuh Syaikhullah; Himmatul Khasanah (Universitas Sulawesi Barat, 2020)
This study aims to assess the physiological response through body surface temperature of Brahman Cross beef by giving different rest periods. This study used 24 Brahman Cross cattle in several slaughterhouses in West Java. Observation of microclimatic conditions includes temperature, humidity, THI (temperature-humidity index). Data collections of livestock body surface temperature was carried out when the cattle arrive at the slaughterhouse, while they are in the holding pen and the restraining box. Comparative tests were carried out on the surface temperature of cows under different conditions using a completely randomized design (CRD). This study showed that the body surface temperature was still in the normal range, between 30.89-36.75 °C. Analysis of variance showed that different rest periods had a significant effect (P <0.05) on body surface temperature change in the eye area in the three pre-cutting stages. Providing a 24 hours rest period resulted in lower stress response in livestock.